2012
DOI: 10.1093/rheumatology/kes184
|View full text |Cite
|
Sign up to set email alerts
|

Comparative effectiveness and predictors of response to tumour necrosis factor inhibitor therapies in rheumatoid arthritis

Abstract: Over 1 year, we found no difference in effectiveness between adalimumab, etanercept and infliximab.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
60
2
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(68 citation statements)
references
References 17 publications
(7 reference statements)
4
60
2
2
Order By: Relevance
“…Observational studies have reported similar effectiveness at 24 weeks to that seen in our study for etanercept [30], and similar CDAI remission (18%) to our study when patients with RA were treated with adalimumab or etanercept for 12 months [31][32][33]. However, other studies have documented greater remission as measured by the CDAI for treatment with etanercept (35%) at 3 years and for adalimumab (27%) at 12 weeks [29,34].…”
Section: Discussionsupporting
confidence: 85%
“…Observational studies have reported similar effectiveness at 24 weeks to that seen in our study for etanercept [30], and similar CDAI remission (18%) to our study when patients with RA were treated with adalimumab or etanercept for 12 months [31][32][33]. However, other studies have documented greater remission as measured by the CDAI for treatment with etanercept (35%) at 3 years and for adalimumab (27%) at 12 weeks [29,34].…”
Section: Discussionsupporting
confidence: 85%
“…A majority of studies classified smoker or non-smoker by smoking status at the time of drug initiation, but some studies considered ex-smoking status. [7,8,[10][11][12] Some studies defined the amount of smoking as more than 5 cigarettes per day within 6 months from initiation of drug administration, [16,19,20,28,29] more than 7 cigarettes per week, [18,26] more than 1 cigarette per day, [17] or the presence of smoking without considering cigarette numbers. [13][14][15][22][23][24][25]27,[31][32][33][34] These variable smoking definitions could contribute to the discrepancy in the study results.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 28 articles were finally selected. Among them, 6 articles were for RA [7][8][9][10][11][12] and 22 articles were for CD. Figure 1 shows the literature selection flows.…”
Section: Literature Selectionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is reinforced by the therapeutic efficacy of rituximab, an anti-CD20 monoclonal antibody that specifically depletes B cells [7]. Other biologic treatments such as tumor necrosis factor (TNF) antagonists and the interleukin (IL)-6 receptor blocking antibody, tocilizumab, have also proven to be clinically effective in RA [8,9] by interfering with specific cytokine dependent mechanisms. In addition, both TNF and IL-6 can have B cell regulatory effects.…”
Section: Introductionmentioning
confidence: 99%